Anti-CD38 Antibody Therapy: Windows of Opportunity Yielded by the Functional Characteristics of the Target Molecule - Antonella Chillemi; Gianluca Zaccarello; Valeria Quarona; Manuela Ferracin; Chiara Ghimenti; Massimo Massaia; Alberto L. Horenstein; Fabio Malavasi (BMC, 2013)
Abstract In vivo use of monoclonal antibodies (mAbs) has become a mainstay of routine clinical practice in the treatment of various human diseases. A number of molecules can serve as targets, according to the condition being treated. Now entering human clinical trials, CD38 molecule is a particularly attractive target because of its peculiar pattern of expression and its twin role as receptor and ectoenzyme. This review provides a range of analytical perspectives on the current progress in and challenges to anti-CD38 mAb therapy. We present a synopsis of the evidence available on CD38, particularly in myeloma and chronic lymphocytic leukemia (CLL). Our aim is to make the data from basic science helpful and accessible to a diverse clinical audience and, at the same time, to improve its potential for in vivo use. The topics covered include tissue distribution and signal implementation by mAb ligation and the possibility of increasing cell density on target cells by exploiting information about the molecule's regulation in combination with drugs approved for in vivo use. Also analyzed is the behavior of CD38 as an enzyme: CD38 is a component of a pathway leading to the production of adenosine in the tumor microenvironment, thus inducing local anergy. Consequently, not only might CD38 be a prime target for mAb-mediated therapy, but its functional block may contribute to general improvement in cancer immunotherapy and outcomes.